Why does parents’ involvement in youth’s learning vary across elementary, middle, and high school? - Wei, Jun; Pomerantz, Eva M.; Ng, Florrie Fei-Yin; Yu, Yanhong; Wang, Mingzhu; Wang, Qian (Contemporary educational psychology, 2019)
•Both types of parents’ involvement were lower in later years of school.•Decrease in parents’ homework assistance was greater than academic socialization.•Youth, parent, and contextual factors all contributed to the involvement decrease.•Youth’s invitations made the largest contribution to the involvement decrease. This research examined why parents’ involvement in youth’s learning varies as youth progress through school. 3074 Chinese youths (M age = 13.89 years) in elementary, middle, and high school and their parents reported on parents’ homework assistance and academic socialization. Youth and parents also reported on potential mechanisms underlying variation in these two types of involvement over the school years. Parents’ homework assistance and academic socialization were both higher in elementary than middle school in which they were higher than high school. Youth’s invitations for involvement, along with parents’ involvement role beliefs, involvement self-efficacy, and perceived involvement norms contributed to the tendency for the two types of involvement to be higher in elementary than middle school. Only youth’s invitations and parents’ perceived norms contributed to the tendency for the two to be higher in middle than high school.